2020
DOI: 10.1126/sciadv.aba0694
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing mitochondrial complex III using alternative oxidase inhibits acute pulmonary oxygen sensing

Abstract: Mitochondria play an important role in sensing both acute and chronic hypoxia in the pulmonary vasculature, but their primary oxygen-sensing mechanism and contribution to stabilization of the hypoxia-inducible factor (HIF) remains elusive. Alteration of the mitochondrial electron flux and increased superoxide release from complex III has been proposed as an essential trigger for hypoxic pulmonary vasoconstriction (HPV). We used mice expressing a tunicate alternative oxidase, AOX, which maintains electron flux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…intestinalis AOX in mitochondria of fruit flies [23][24][25] and mice [28][29]. The same applies to the mouse MRC complex III deficiency [9,11]. .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…intestinalis AOX in mitochondria of fruit flies [23][24][25] and mice [28][29]. The same applies to the mouse MRC complex III deficiency [9,11]. .…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, it is suggested that AOX can bypass blockade or deficiency of the MRC complexes III and IV by restoring electron flow upstream of the MRC complex III. Consequently, AOX is considered to be an important element of a therapeutic strategy against impairment of these complexes [1,3,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…So far two other animal models, both obtained due to heterologous expression of the tunicate C. intestinalis AOX in fruit ies and mice, have been used in research on AOX impact on animal physiology and the enzyme possible application in therapy of human mitochondrial diseases (e.g. [1,3,[9][10][11][12]. The data obtained for H. exemplaris could supplement the models due to the presence of native AOX as well as simplicity of the tardigrade culture and AOX research in intact specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility to provide a complete or substantial protection against a range of phenotypes induced by the MRC complex IV de ciency or inhibition was also observed after expression of C. intestinalis AOX in mitochondria of fruit ies [23][24][25] and mice [28][29]. The same applies to the mouse MRC complex III de ciency [9,11]. .…”
mentioning
confidence: 95%
See 1 more Smart Citation